AN ANALYSIS FLOUTING MAXIM USED IN THE BOSS BABY: FAMILY BUSSINES MOVIE SCRIPT - Sinabutar, Willa Cecilia Nikensitara; Sari, Dian Purnama (STBA Prayoga Padang, 2023)
Abstract Studying the several maxims that are flouted in the script for the film The Boss Baby: Family Business was the aim of the study. People must adhere to maxims when conversing; when they do not, it is referred to as flouting the maxim. Not all flaunting maxims are negative. People generally utilize flouting maxims for amusement, despite the fact that they can lead to misunderstandings. To get a comprehensive result, this study employed a qualitative research design. The data were gathered by the researchers through non-participant observation. The researchers classified the data according to the categories of maxims that the data violated by using Grice's theory as a guide. The researchers discovered 35 pieces of data that fit into several categories of maxims that were broken in the screenplay. The various forms of maxims that are disregarded in the film script include maxims of quantity with 3 data, flouting maxim of quality with 5 data, flouting maxim of relevance with 25 data, flouting maxim of manner with 3 data.